Myocutaneous bipedicled flap, a free tarsoconjunctival graft, and a free skin graft for reconstruction of subtotal upper lid defects - Šarenac, Tomislav (Acta Medico-Biotechnica, 2023)
Purpose: To evaluate and present the outcomes of a single-step approach using a free tarsoconjunctival graft, a myocutaneous bipedicled flap, and a free skin graft for the reconstruction of subtotal upper eyelid defects following tumor excision. Methods: This retrospective case series involved four patients who underwent upper eyelid reconstruction after tumor surgery. The defect affected 50%─75% and > 75% of the eyelid in two patients each. Among the latter patients, the lateral and medial canthus were involved in one patient each. The posterior lamella was reconstructed using the contralateral upper eyelid tarsoconjunctival graft, which was attached to the levator muscle at the site of the defect. The levator was weakened and elongated using small myotomies in one patient. The anterior lamella was reconstructed with a myocutaneous bipedicled flap based laterally and medially, leaving an exposed area beneath the brow, which was covered with a free skin graft. Results: The patients had successful non-necrotizing healing and achieved satisfactory cosmetic outcomes. None of the patients developed clinically significant lagophthalmos, which would have required lubrication. Normal levator function was achieved in all patients. Two patients required additional surgery to repair pseudotrichiasis. Conclusion: Subtotal upper eyelid defects could be effectively reconstructed using a combination of a free tarsoconjunctival graft, a bipedicled myocutaneous flap, and a free skin graft. Two-step procedures could be avoided in most cases by using this method.